ISLAM DAN SAINS: ANTARA ISLAMISASI ILMU, PENGILMUAN ISLAM, DAN TRANSINTEGRASI ILMU - Saripuddin Saripuddin; ahmad syukri; Badarussyamsi Badarussyamsi (UIN Sunan Kalijaga Yogyakarta, 2021)
This article discusses a comparative study between the Islamization of knowledge, Islamic science, and the transintegrasi of sciences. What are the similarities and differences between the three? Why do the three of them have different views about the form of the encounter between science and Islam? To answer this question, this article uses an epistemological and historical approach. This article finds that there are two similarities between the three, namely they an Islamic response to the development of science and they reject secularism. Meanwhile, the difference between the three lies in the emphasis and the details of the key concepts. The difference between the three occurs because of the different epistemological and historical backgrounds between the three.